Assessment of participation bias in cohort studies: systematic review and meta-regression analysis - Sérgio Henrique Almeida da Silva Junior; Simone M. Santos; Cláudia Medina Coeli; Marilia Sá Carvalho (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
Abstract The proportion of non-participation in cohort studies, if associated with both the exposure and the probability of occurrence of the event, can introduce bias in the estimates of interest. The aim of this study is to evaluate the impact of participation and its characteristics in longitudinal studies. A systematic review (MEDLINE, Scopus and Web of Science) for articles describing the proportion of participation in the baseline of cohort studies was performed. Among the 2,964 initially identified, 50 were selected. The average proportion of participation was 64.7%. Using a meta-regression model with mixed effects, only age, year of baseline contact and study region (borderline) were associated with participation. Considering the decrease in participation in recent years, and the cost of cohort studies, it is essential to gather information to assess the potential for non-participation, before committing resources. Finally, journals should require the presentation of this information in the papers.